Pelangaran Outsourcing Yang Dapat Dikategorikan Sebagai Tindak Pidana Perdagangan Orang - Alexander Simon Pally (Faculty of Law, Universitas Pattimura, 2019)
This study discusses Outsourcing violations which can be categorized as Trafficking in Persons. In this writing, outsourcing workers employed need to get legal protection in accordance with the mandate of Article 27 paragraph (2) of the 1945 Constitution stating